2019
DOI: 10.1111/jwas.12603
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic toxicity of nitrate to fat greenling (Hexagrammos otakii) juveniles

Abstract: We evaluated the acute and chronic toxicity of nitrate to juvenile fat greenling Hexagrammos otakii. The 24‐, 48‐, 72‐, and 96‐hr LC50s of nitrate to 1.91 ± 0.7 g greenlings were 2,741, 2,413.5, 2,357.6, or 2,339.2 mg/L nitrate‐N, respectively. Greenlings (6.55 ± 1.83 g) were exposed to 5 mg/L (control) and 157 mg/L for 4 weeks in a recirculating aquaculture system. After 4 weeks, length, weight, feed conversion ratio, and specific growth rate were significantly (p < 0.05) lower for nitrate‐exposed fish than f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…DOI: https://doi.org/10.1086/713252 kPa) and their blood-carrying capacity (lower hemoglobin concentration, HB]; and hematocrit, HCT) was marginally impaired. Exposure to other nitrogenous waste products (nitrite, ammonia) have also been shown to disrupt regular cardiorespiratory function (causing hyperventilation, tachycardia; Aggergaard and Jensen 2001; Williams et al 1997), while nitrate exposure has been shown to lower the blood-carrying capacity of various fishes via the formation of methemoglobin, and reductions in functional [HB] and HCT (Aboagye and Allen 2014;Gomez Isaza et al 2020b;Monsees et al 2017;Yang et al 2019). Indeed, in our previous study, we found that silver perch exposed to identical nitrate concentrations (50 and 100 mg NO 3 − L -1 ) experienced significant methemoglobin formation (20 -34% methemoglobin in the blood) and indicates that silver perch are susceptible long-term nitrate exposures (Gomez Isaza et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DOI: https://doi.org/10.1086/713252 kPa) and their blood-carrying capacity (lower hemoglobin concentration, HB]; and hematocrit, HCT) was marginally impaired. Exposure to other nitrogenous waste products (nitrite, ammonia) have also been shown to disrupt regular cardiorespiratory function (causing hyperventilation, tachycardia; Aggergaard and Jensen 2001; Williams et al 1997), while nitrate exposure has been shown to lower the blood-carrying capacity of various fishes via the formation of methemoglobin, and reductions in functional [HB] and HCT (Aboagye and Allen 2014;Gomez Isaza et al 2020b;Monsees et al 2017;Yang et al 2019). Indeed, in our previous study, we found that silver perch exposed to identical nitrate concentrations (50 and 100 mg NO 3 − L -1 ) experienced significant methemoglobin formation (20 -34% methemoglobin in the blood) and indicates that silver perch are susceptible long-term nitrate exposures (Gomez Isaza et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…reduction in the interlamellar cell mass; Borowiec et al 2015; Dhillon et al 2020a). Primarily, nitrate can results in the oxidation of hemoglobin to a nonoxygen binding form, methemoglobin, which generates tissue hypoxia and can be fatal at extreme levels (Camargo et al 2005;Monsees et al 2017;Yang et al 2019). High levels of nitrate also reduce concentrations of functional hemoglobin, lower hematocrit, and alter hemoglobinoxygen binding affinities (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When water-nitrate concentrations are elevated, nitrate enters the body of aquatic animals passively through the gill epithelium and accumulates in plasma (Stormer et al, 1996). Inside the body, nitrate can lower concentrations of functional haemoglobin, via the oxidation of the central iron ion (Fe 2+ to Fe 3+ ), to a non-oxygen binding form, methaemoglobin (Monsees et al, 2017;Yang et al, 2019). Elevated concentrations of methaemoglobin cause an inherent loss of oxygen transport capacity (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogenous contamination of surface waters is a serious environmental problem, causing eutrophication of rivers, lakes, and near-shore marine environments [1,2] and raising the likelihood of toxic algal blooms in receiving waters [3,4]. Accumulation of nitrogenous wastes is also a problem in aquaculture systems [5], posing toxicity to cultured organisms [6][7][8][9]. Microbially mediated nitrification in biofilters is commonly used to convert ammonia-N to nitrite-N and further to nitrate-N [10].…”
Section: Introductionmentioning
confidence: 99%